2020
DOI: 10.1371/journal.pone.0230979
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological and prognostic value of the pretreatment neutrophil-to-lymphocyte ratio in small cell lung cancer: A meta-analysis

Abstract: Although many scholars have recently studied the relationships between the pretreatment neutrophil-to-lymphocyte ratio (NLR) and prognosis in patients with small cell lung cancer (SCLC), the conclusions have been inconsistent. Accordingly, in this meta-analysis, we attempted to assess the clinicopathological and prognostic value of the pretreatment NLR in SCLC. Related literature was searched using PubMed, Embase, Cochrane Library, Web of Science, Chinese Biomedical Literature, China National Knowledge Infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
5
27
1
Order By: Relevance
“…Our analysis demonstrated that the NLR before surgical resection of NSCLC might reflect the invasiveness of tumours. Higher NLR was associated with advanced cancer stage, which is consistent with the results of a current meta-analysis 4 . Our results further showed preoperative NLR was also linked to worse differentiation, and presence of perineural infiltration.…”
Section: Continuous Nlrsupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis demonstrated that the NLR before surgical resection of NSCLC might reflect the invasiveness of tumours. Higher NLR was associated with advanced cancer stage, which is consistent with the results of a current meta-analysis 4 . Our results further showed preoperative NLR was also linked to worse differentiation, and presence of perineural infiltration.…”
Section: Continuous Nlrsupporting
confidence: 91%
“…Prior studies have reported a variety of inflammation markers as predictors for oncological outcomes in multiple types of cancer . In NSCLC, preoperative NLR, PLR and PNI have been demonstrated to predict cancer recurrence or mortality after tumour resection [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . However, there is little evidence regarding the superior prognostic factor among these inflammation markers in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have showed that NLR and PLR are related to poor prognosis in patients with lung cancer. A meta-analysis demonstrated that high pretreatment NLR was closely related to poorer progression-free survival and overall survival in patients with small-cell lung cancer [ 7 ]. A retrospective descriptive study showed that high PLR was significantly associated with poor overall survival in patients with stage IV non-small-cell lung cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only one systematic review on NLR in SCLC has been performed (56) identifying an association between NLR and OS. In the previous review, 21 studies were included of which six were posters from international conferences and two of these could not be identi ed in the Pubmed, Embase, WOS, or Scopus databases.…”
Section: Discussionmentioning
confidence: 99%